The effect of hydroalcoholic extract of Teucrium polium L. on the inflammatory markers and lipid profile in hypercholesterolemic rats - Amraei M; Ghorbani A; Seifinejad Y; Mousavi SF; Mohamadpour M; Shirzadpour E (Dove Medical Press, 2018)
Mansour Amraei,1,* Ayub Ghorbani,1,* Yaser Seifinejad,1 Seyedeh Fatemeh Mousavi,2 Mahmoud Mohamadpour,3 Ehsan Shirzadpour3 1Department of Physiology, Faculty of Medicine, Ilam University of Medical Sciences, Ilam, Iran; 2Student Research Committee, Ilam University of Medical Sciences, Ilam, Iran; 3Department of Biochemistry, Faculty of Medicine, Ilam University of Medical Sciences, Ilam, Iran *These authors contributed equally to this work Background: Cardiovascular diseases are among the most common causes of mortality worldwide. Therefore, it is necessary to control the risk factors of these patients. Since the level of inflammatory markers and lipid profiles has increased in cardiovascular diseases and due to the increasing role of plants in the treatment of diseases, the current study aimed to investigate the effect of hydroalcoholic extract of Teucrium polium on inflammatory markers and lipid profile in hypercholesterolemic rats.Materials and methods: A total of 24 adult male Wistar rats were randomly divided into four groups of six each and treated with oral administration for 8 weeks. The control group received normal diet, the sham group received high-cholesterol diet and experimental groups 1 and 2 received high-cholesterol diet in the 8 weeks and doses of 85 and 170 mg/kg, respectively, of the T. polium hydroalcoholic extract (TPHAE) in the second 4 weeks. At the beginning and the end of the study, rats were examined for biochemical parameters. The mean level of variables for each group was presented as mean ± standard error of mean.Results: The results of this study showed that, after administration of TPHAE, there was a significant decrease in the mean of inflammatory markers in all groups compared to sham group (P<0.001). Also, administration of the extract significantly reduced the serum levels of triglyceride, cholesterol and LDL-cholesterol and significantly increased the serum HDL-cholesterol levels. In addition, the 170 mg/kg dose of TPHAE was the most effective in reducing serum levels of inflammatory and lipid markers.Conclusion: Treatment with TPHAE caused dose-dependent decrease in serum levels of inflammatory markers and lipid profile in hypercholesterolemic rats. Therefore, it can be applied as a natural product for the management of cardiovascular diseases. Keywords: Teucrium polium, inflammatory markers, lipid profile, male rat